HbF in HbE/β-thalassemia: A clinical and laboratory correlation. Issue 6 (July 2015) - Lim, Wai Feng; Muniandi, Logeswaran; George, Elizabeth; Sathar, Jameela; Teh, Lai Kuan; Lai, Mei I
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction Fetal hemoglobin (HbF) is the predominant hemoglobin in red cells during fetal life. Just after birth, the level of HbF decreases gradually to <1%, and is replaced mainly by adult hemoglobin (HbA) (∼97%). However, higher HbF levels could be associated with HbE/β-thalassemia, a complex thalassemia intermedia with a diverse clinical severity ranging from mild-to-severe anemia. This study investigates the correlation of HbF level with the clinical and laboratory data of HbE/β-thalassemia individuals. Methods Peripheral blood samples from 30 HbE/β-thalassemia subjects were subjected to a full blood count, genomic as well as quantitative real-time polymerase chain reaction gene expression studies. Statistical analyses were performed using SPSS 17.0. Results HbF levels were influenced by age, mean cell volume (MCV), mean cell hemoglobin (MCH), HbA, β-globin, and α/β-globin expressions. Discussion HbF production is affected by the α/β-globin chain imbalance due to the lack of β-globin gene expression as well as inversely correlates to the amount of functional hemoglobin available in the cells.